Materdicine: Interdiscipline of materials and medicine. Issue 3 (16th July 2020) - Xiang, Huijing; Chen, Yu
Abstract: The clinical medicine and biomaterials are two fields that are conducive to achieve the goal of precise medicine on diagnostics and therapeutics of various diseases. The interdiscipline of materials and medicine, termed/abbreviated as "materdicine, " seeks to address the dominant medical shortcomings and challenges faced by conventional medicine, including inferior bioavailability, systemic toxicity, poor targeting specificity, and unsatisfied diagnostic/therapeutic efficacy. In this review, we present the perspective and discussion on the use of diverse biomaterials for disease diagnosis and treatment from a broad perspective, especially on nanoscale biomaterials. We initially highlight the recent advances on the engineering of abundant contrast agents for diagnostic bioimaging, such as optical fluorescence imaging, magnetic resonance imaging, and photoacoustic imaging. In addition, discussions on the diagnostic biosensing for point‐of‐care diagnosis, such as fluorescent and plasmonic sensors, are supplemented. Furthermore, we outline several materdicine‐enabled therapeutic modalities for disease treatments, including the following exemplified scaffold biomaterials for regenerative medicine. Especially, rational modulation of toxicity issues of micro‐/nanoscale biomaterials is also accounted for addressing the possible concerns of biocompatibility and biosafety on further clinical translation of materdicine. Finally, we summarize facing challenges and outlook future developments relating to the clinical translation of these distinctive biomaterials in materdicine. Abstract : This review proposes and highlights the perspective of materdicine, providing a deep discussion on the rational design, construction, and application of versatile biomaterials/medmaterials with unique physiochemical property and specific biological effects for disease diagnosis and treatment from a broad perspective, especially on nanoscale biomaterials.